Effect of ethanol-assisted mixing on the selected properties and homogeneity of NR/BR blends - Meng, Chao (Polimery, 2023)
The effect of the mixing method (normal and ethanol-assisted) on selected properties of natural rubber with butadiene rubber blends (NR/BR 80/20) was investigated. Scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR) and thermogravimetric analysis (TGA) were used to evaluate the properties. In addition, the mechanical tensile properties, tear resistance and thermal aging, as well as vulcanization characteristic were determined. It was found that ethanol-assisted mixing can significantly improve the mechanical properties and thermal stability of the blends as a result of better dispersion of additives in the rubber matrix.